2016
DOI: 10.3382/ps/pew065
|View full text |Cite
|
Sign up to set email alerts
|

Lower expression of sialic acid receptors in the cecum of silky fowl (Gallus gallus domesticus Brisson) compared to white leghorn

Abstract: Avian influenza virus has received increasing attention in recent years because of the potential for recombination with the human virus. Distributions of sialic acid receptors on target cells are determinants of the susceptibilities of different species to influenza virus infection. In this study, the distribution of sialic acid receptors in the respiratory and gastrointestinal tracts of Silky Fowl and White Leghorn chickens were compared. The results showed that sialic acid-α-2,3-galactose receptors and siali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, in the present study, the reduced expression of genes was related to the Toll-like and NOD-like receptor pathways, which might result from the proliferation, rather than the differentiation, of B-cells in the BF. Our recent studies also demonstrated that a few immune cells in the cecum of SF were closely related to the reduced expression of sialic acid receptors 27 .…”
Section: Discussionmentioning
confidence: 61%
“…However, in the present study, the reduced expression of genes was related to the Toll-like and NOD-like receptor pathways, which might result from the proliferation, rather than the differentiation, of B-cells in the BF. Our recent studies also demonstrated that a few immune cells in the cecum of SF were closely related to the reduced expression of sialic acid receptors 27 .…”
Section: Discussionmentioning
confidence: 61%
“…Macrophages express Gal-specific receptors (39), which could explain the higher abundance of SAα2,3Gal in the cecum of infected birds relative to controls. Evidence of macrophages expressing Gal-specific receptors are seen in white leghorn chickens, which in one study had a greater abundance of sialic acid receptors than silky fowl because of a higher number of immune cells in the leghorns' cecum (40). The cecum has a unique response to LPAIV infection compared to other intestinal tissues, which warrants further analysis of SAα2,3Gal in this tissue.…”
Section: Two Hypotheses Could Explain the Negative Relationship Betweenmentioning
confidence: 94%
“…Macrophages express Galspecific receptors [38], which could explain the higher abundance of SAα2,3Gal in the cecum of infected birds relative to controls. Evidence of macrophages expressing Gal-specific receptors are seen in white leghorn chickens, which in one study had a greater abundance of sialic acid receptors than silky fowl because of a higher number of immune cells in the leghorns' cecum [39]. The cecum has a unique response to LPAIV infection compared to other intestinal tissues, which warrants further analysis of SAα2,3Gal in this tissue.…”
Section: Discussionmentioning
confidence: 94%